2016
DOI: 10.4137/becb.s31601
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Networks as Decision Support Tools in Cytopathology: Past, Present, and Future

Abstract: OBJECTIVEThis study aims to analyze the role of artificial neural networks (ANNs) in cytopathology. More specifically, it aims to highlight the importance of employing ANNs in existing and future applications and in identifying unexplored or poorly explored research topics.STUDY DESIGNA systematic search was conducted in scientific databases for articles related to cytopathology and ANNs with respect to anatomical places of the human body where cytopathology is performed. For each anatomic system/organ, the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 99 publications
(110 reference statements)
0
40
0
2
Order By: Relevance
“…Other research groups have performed morphometric and machine-learning analyses of urine cytology specimens supporting the validity of the NC ratio as a marker of atypia and demonstrating the utility and accuracy of neural networks in relation to urinary cytology images. [15][16][17][18][19][20][21] These studies mainly demonstrate the diagnostic and prognostic utility of morphometry and machine learning in isolation.…”
Section: Comparison With Other Automated/ Semiautomated Systemsmentioning
confidence: 99%
“…Other research groups have performed morphometric and machine-learning analyses of urine cytology specimens supporting the validity of the NC ratio as a marker of atypia and demonstrating the utility and accuracy of neural networks in relation to urinary cytology images. [15][16][17][18][19][20][21] These studies mainly demonstrate the diagnostic and prognostic utility of morphometry and machine learning in isolation.…”
Section: Comparison With Other Automated/ Semiautomated Systemsmentioning
confidence: 99%
“…32,33 To achieve this, various techniques have been tested so far, involving either classical statistical models or more advanced techniques, such as neural networks. 23,[34][35][36][37] The present results are encouraging in the context of supplementing the performance of cytology in the diagnosis of endometrial cancer. [38][39][40][41] Nuclear morphological characteristics seem to play a central role in endometrial cytology, a finding which has been also observed in our previous studies.…”
Section: Discussionmentioning
confidence: 64%
“…Its implementation in endometrial cytological analysis appears to help overcoming the subjective nature of the standard evaluation, which is related to the lack of consensus in the measuring process, resulting in poor reproducibility, and significant interobserver and intraobserver variability . To achieve this, various techniques have been tested so far, involving either classical statistical models or more advanced techniques, such as neural networks …”
Section: Discussionmentioning
confidence: 99%
“…There are numerous mechanical learning techniques that have been applied to solve cytopathology problems [8,9,10]. For this study, we selected Classification and Regression Trees (CARTs) [8,11] due to their ability to produce relatively simple, understandable rules.…”
Section: Introductionmentioning
confidence: 99%
“…For this study, we selected Classification and Regression Trees (CARTs) [8,11] due to their ability to produce relatively simple, understandable rules. Such rules can be applied as a guideline in everyday practice, and thus help cytopathologists to choose the required immunocytochemistry staining for ancillary techniques during diagnosis and to be aware of the uncertainty of diagnosis in each step.…”
Section: Introductionmentioning
confidence: 99%